Pengembangan Wisata Kreatif Melalui Galeri Batik TIN di Kelurahan Gundih Kota Surabaya - Damayanti, Fira Alfiana; Ma’ruf, Muhammad Farid (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Role of Community Empowerment can help improve the ability and utilize the potential resources available to solve the problems faced. The Surabaya City Government created the Batik TIN Gundih program. This type of research uses descriptive qualitative research to analyze the development of creative tourism at the TIN Batik Gallery based on empowerment through SMEs in Gundih Village, Surabaya City. This study analyzes the potential, benefits, and obstacles in tourism development efforts, the focus of this research is seen from the elements of tourism development proposed by (Suwantoro, 1997) which involves five main indicators, namely tourist objects and attractions, tourist infrastructure, tourist facilities, management or infrastructure, and society or environment. The results of the study indicate that this Batik Gallery as a whole has very great potential to be developed in the future into an advanced and leading creative tourism destination in the city of Surabaya. During the three years of implementation, there are still several obstacles such as the lack of recognition of Batik TIN Gundih as a creative tourism destination and batik production in the city of Surabaya due to the lack of digitalization management and promotion, the lack of adequate supporting facilities and infrastructure, the absence of a professional institutional system and legal umbrella for tourism, and the limited human resources (HR) of the participating community, especially the competent young generation. Therefore, support from the Surabaya City Government, improvement of infrastructure and facilities, and internal development of HR of Batik TIN UMKM administrators are the keys to developing this creative tourism.